Selective Oxidation of Alkyl Benzenes Using CrO3 Combined with Ce(SO4)2 - Song, Guang-Liang; Liu, Yuan-Yuan; Chen, Lei; Zhu, Hong-Jun (Asian Journal of Chemistry, 2010)
A novel system of oxidant-CrO3 combined with Ce(SO4)2, has been demonstrated to be an effective and economic oxidant for the oxidation of alkyl benzenes to ketones or aldehydes with little by-products and high yields. Including 1-(2,4-diethylphenyl)ethanone (3), seven alkyl benzenes have been studied, the products have been characterized by the elemental analyses, 1H, 13C NMR and EI-MS. The possible mechanisms of this oxidation reaction were also proposed. The obtained 5-acetyl-3-methylisobenzofuran-1(3H)-one (5), the by-product of 3 was also confirmed by the crystal structure.